Manajemen Komunikasi dalam Menangani Stunting melalui Penggalakan Posyandu - Ariyanti, Putri Erlinda; Pardianto, Pardianto (Journal of Management, Education and Communication, 2025)
Stunting is a complex public health issue that requires cross-sectoral handling, especially at the village level. This study aims to examine the role of communication management in stunting prevention efforts through the promotion of Posyandu activities in Pesawahan Village, Tiris Subdistrict, Probolinggo Regency. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results of the study show that the success of the stunting eradication program through the communication management process carried out by Adalah is as follows: 1). Collaborating with community health centers to provide assistance to cadres. 2). Assistance from posyandu cadres to stunted toddlers. 3). Communication-based monitoring and evaluation. In addition, the synergy between traditional and digital communication media helps reinforce the health messages conveyed.